Direct decompositions of artinian modules related to formations of groups - Kurdachenko, L. A.; Otal, J. (Algebra and Discrete Mathematics, 2003)
We survey direct decompositions of artinian modules over group rings into two summands where all the chief factors of the first are X–central and all the chief factors of the other is X–eccentric, where X is a certain formation of finite groups.